Spectrofluorometric determination of linagliptin in bulk and in pharmaceutical dosage form - El-Bagary, Ramzia Ismail; Elkady, Ehab Farouk; Ayoub, Bassam Mahfouz (European Journal of Chemistry, 2014)
Simple and precise spectrofluorometric method has been developed and validated for the determination of linagliptin (LNG) in the range of 10-110 μg/mL. The results obtained were of good precision and statistically compared to the reference method using one-way analysis of variance (ANOVA). The method developed was satisfactorily applied to the analysis of the pharmaceutical formulation and proved to be specific and accurate for the quality control of linagliptin in its pharmaceutical dosage form. The development of spectrofluorometric method for the determination of LNG was of interest as no such methods have been reported.